Tax systems taxpayer compliance and specific tax issues - Mohd Hanefah, Mustafa (Penerbit Universiti Utara Malaysia, 2007)
This book has eight chapters. Each chapter discusses one topic related to taxation. The topics covered in this book are tax systems, taxpayer compliance, compliance costs, transfer pricing, accounting malpractices and tax issues, taxation of ecommerce, and electronic tax administration. These topics are relevant to the advanced taxation course in the under-graduate and post-graduate programs (Masters and PhD). Each topic is discussed with relevant literature. The first three chapters touch on issues and problems related to the new tax administrative system i.e the self-assessment system, which is being implemented in developed countries including Malaysia, and is now being adopted for implementation in many developing countries worldwide. Chapters 2, 3 and 4 give an insight to issues related to tax systems, taxpayer compliance and compliance costs. The other four chapters – 5, 6, 7 and 8 discuss topics that are categorised as selected tax issues. The selected tax issues include transfer pricing, accounting malpractices and tax issues, taxation of ecommerce and electronic tax administration. These issues have not been deliberated before, and it is timely that a book of this nature is published for tax authorities, researchers, students, lecturers, authorities and practitioners. Past literature and research findings are quoted to support the discussions in each chapter. The author’s own research findings in certain topics found in this book are used to support the arguments and discussions.